Non-Invasive whole-body detection of complement activation using radionuclide imaging in a mouse model of myocardial ischaemia-reperfusion injury. Issue 1 (December 2017) - Sharif-Paghaleh, Ehsan; Yap, May; Puhl, Sarah-Lena; Badar, Adam; Torres, Julia; Chuamsaamarkkee, Krisanat; Kampmeier, Florian; Smith, Richard; Clark, James; Blower, Philip; Sacks, Steven; Mullen, Gregory
Abstract Complement activation is a recognised mediator of myocardial ischaemia-reperfusion-injury (IRI) and cardiomyocytes are a known source of complement proteins including the central component C3, whose activation products can mediate tissue inflammation, cell death and profibrotic signalling. We investigated the potential to detect and quantify the stable covalently bound product C3d by external body imaging, as a marker of complement activation in heart muscle in a murine model of myocardial IRI. We used single-photon-emission-computed-tomography (SPECT) in conjunction with99m Technecium-labelled recombinant complement receptor 2 (99m Tc-rCR2), which specifically detects C3d at the site of complement activation. Compared to control imaging with an inactive CR2 mutant (99m Tc-K41E CR2) or an irrelevant protein (99m Tc-PSMA) or using99m Tc-rCR2 in C3-deficient mice, the use of99m Tc-rCR2 in complement-intact mice gave specific uptake in the reperfused myocardium. The heart to skeletal muscle ratio of99m Tc-rCR2 was significantly higher than in the three control groups. Histological analysis confirmed specific uptake of99m Tc-rCR2. Following therapeutic inhibition of complement C3 activation, we found reduced myocardial uptake of99m Tc-rCR2. We conclude, therefore that99m Tc-rCR2 imaging can be used for non-invasive detection of activated complement and in future could be exploited to quantify the severity of myocardial damage due to complement activation.